2011
DOI: 10.1016/j.jtcvs.2010.06.023
|View full text |Cite
|
Sign up to set email alerts
|

The collateral network concept: A reassessment of the anatomy of spinal cord perfusion

Abstract: OBJECTIVE Prevention of paraplegia following repair of thoracoabdominal aortic aneurysms (TAAA) requires understanding the anatomy and physiology of the blood supply to the spinal cord. Recent laboratory studies and clinical observations suggest that a robust collateral network must exist to explain preservation of spinal cord perfusion when segmental vessels are interrupted. An anatomical study was undertaken. METHODS Twelve juvenile Yorkshire pigs underwent aortic cannulation and infusion of a low-viscosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
171
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(186 citation statements)
references
References 25 publications
1
171
0
4
Order By: Relevance
“…CSF drainage was used in these 7 patients (extent I or II; 100%), and in 1 of the 2 patients with DTA only (1 of 2; 50%). The results of our study support the collateral network concept described by Griepp and colleagues 13 ; occlusion of the collateral flow from the LSCA or hypogastric artery may influence spinal cord ischemia, 11 and mild or moderate hypothermia alone may not afford sufficient spinal cord protection during the clamping period. This hypothesis is also supported by data from the European Registry on Endovascular Aortic Repair Complications, 23 which showed that extensive coverage of intercostal arteries alone was not associated with spinal cord injury, but simultaneous closure of the collateral vascular territories was highly related to the development of spinal cord injury.…”
Section: Higher Rate Of Paraplegia In the Ac Groupsupporting
confidence: 83%
See 1 more Smart Citation
“…CSF drainage was used in these 7 patients (extent I or II; 100%), and in 1 of the 2 patients with DTA only (1 of 2; 50%). The results of our study support the collateral network concept described by Griepp and colleagues 13 ; occlusion of the collateral flow from the LSCA or hypogastric artery may influence spinal cord ischemia, 11 and mild or moderate hypothermia alone may not afford sufficient spinal cord protection during the clamping period. This hypothesis is also supported by data from the European Registry on Endovascular Aortic Repair Complications, 23 which showed that extensive coverage of intercostal arteries alone was not associated with spinal cord injury, but simultaneous closure of the collateral vascular territories was highly related to the development of spinal cord injury.…”
Section: Higher Rate Of Paraplegia In the Ac Groupsupporting
confidence: 83%
“…11,12 Furthermore, temporary occlusion of the left subclavian artery (LSCA) may potentially reduce spinal cord perfusion and increase the risk of spinal cord ischemic injury. 11,13 There is currently no consensus on the optimal method for proximal control in open repair of DTA/TAAA involving the distal arch, and previous studies on this topic have been limited. Thus, the aim of this study was to compare the clinical outcomes of DHCA versus AC in the surgical repair of DTA/TAAA involving the distal arch.…”
mentioning
confidence: 99%
“…The posterior radicular artery follows a anterior radicular artery anterior radicular a., 9,10,20 medullary a., 12 anterior medullary a., 18 anterior radiculomedullary aa., 16,17 a. radicular anterior, 19 anterior spinal canal a., segmental a. 21 Ramo radicular anterior (TA)…”
Section: Review Of the Literatureunclassified
“…It is no longer believed that preservation of flow to a solitary critical artery is enough to protect the spinal cord. Rather, the SAs are part of a more extensive paraspinal and intraspinal collateral network which is fed predominantly from the sub-clavian artery branches from above, and from the hypogastric artery branches from below [18]. Experimental studies have demonstrated that the collateral network undergoes remodelling after extensive segmental artery sacrifice with an increase in the diameter of the spinal artery within 24 h and further enlargement by nearly 100% within 5 days [19].…”
Section: Discussionmentioning
confidence: 99%